Sequencing KRT71 as a candidate gene for hair shape variation in dromedary camels (Kuwait Journal of Science)
Mammalian breeds within different species display a distinct variation in hair shape. Genetic variants within the Keratin 71 (KRT71) gene were linked to curly hair in multiple species, making it a suitable candidate for investigating hair shape in under-studied species like the dromedary camel. Hair shape has been recently characterized in dromedary camels and classified into five categories: straight, C-shaped, wavy, ringed, and kinky. The objective of this study was to (1) sequence the coding regions of KRT71 gene (i.e., exons and intronic splicing regions) using a group of dromedary camels of different hair shapes, (2) identify polymorphisms, and (3) examine the relationship between the identified polymorphisms and hair shape. Tail-hair samples were collected from 102 different Arabian Peninsula camel-types and their DNA was extracted. For each individual camel, the coding and intronic splice regions of the KRT71 gene were amplified using multiple PCR reactions and the PCR products were then Sanger sequenced. The alignment of the generated sequences across the sampled 102 camels revealed a total of seventeen polymorphisms, five of which were in the coding region. Although some of these polymorphisms caused amino acid alterations, none of them fully explained the different hair shape categories in the dromedary camel. However, the identified variants may work and interact with variants in other genes to control hair shape. This study is the first to investigate hair shape genetics in dromedary camels, providing the basis for future selective breeding programs. © 2025 The Authors